Diffusion Kurtosis Imaging Detects Microstructural Changes in a Methamphetamine-Induced Mouse Model of Parkinson's Disease - Arab, Anas; Ruda-Kucerova, Jana; Minsterova, Alzbeta; Drazanova, Eva; Szabó, Nikoletta; Starcuk, Zenon; Rektorova, Irena; Khairnar, Amit (Neurotoxicity research, 2019)
Methamphetamine (METH) abuse is known to increase the risk of Parkinson's disease (PD) due to its dopaminergic neurotoxicity. This is the rationale for the METH model of PD developed by toxic METH dosing (10 mg/kg four times every 2 h) which features robust neurodegeneration and typical motor impairment in mice. In this study, we used diffusion kurtosis imaging to reveal microstructural brain changes caused by METH-induced neurodegeneration. The METH-treated mice and saline-treated controls underwent diffusion kurtosis imaging scanning using the Bruker Avance 9.4 Tesla MRI system at two time-points: 5 days and 1 month to capture both early and late changes induced by METH. At 5 days, we found a decrease in kurtosis in substantia nigra, striatum and sensorimotor cortex, which is likely to indicate loss of DAergic neurons. At 1 month, we found an increase of kurtosis in striatum and sensorimotor cortex and hippocampus, which may reflect certain recovery processes. Furthermore, we performed tract-based spatial statistics analysis in the white matter and at 1 month, we observed increased kurtosis in ventral nucleus of the lateral lemniscus and some of the lateral thalamic nuclei. No changes were present at the early stage. This study confirms the ability of diffusion kurtosis imaging to detect microstructural pathological processes in both grey and white matter in the METH model of PD. The exact mechanisms underlying the kurtosis changes remain to be elucidated but kurtosis seems to be a valuable biomarker for tracking microstructural brain changes in PD and potentially other neurodegenerative disorders.
Keywords: Behavior, Animal; modely nemocí na zvířatech; Male; Behaviour; Dopamine Agents; Parkinsonova nemoc sekundární; difuzní magnetická rezonance; Brain; MRI; Parkinson’s disease; dopaminové látky; mužské pohlaví; methamfetamin; Animals; Methamphetamine; Diffusion Magnetic Resonance Imaging; zvířata; myši inbrední C57BL; Disease Models, Animal; Tract-based spatial statistics; mozek; chování zvířat; Mice, Inbred C57BL; Parkinson Disease, Secondary; Mice; Diffusion kurtosis imaging